Optimising nitrogen use efficiency of prilled urea through integrated use of nano-ZnO and green manuring for better productivity, quality and nutritional status of Basmati rice crop - Baral, Kirttiranjan; Shivay, Yashbir Singh; Prasanna, Radha; Kumar, Dinesh; Srinivasarao, Cherukumalli; Mandi, Sunil; Nayak, Somanath; Reddy, Kadapa Sreenivasa (Frontiers in Sustainable Food Systems, 2024)
In agricultural systems, nitrogen (N) losses from traditional fertilizers threaten food security. A new approach uses nanoparticles (NPs) coatings on urea to increase N availability and potentially improve crop yields. A field experiment in Basmati rice was conducted at the ICAR-Indian Agricultural Research Institute, New Delhi, India (2020-2021) using a split plot design. The study evaluated two summer green manure (GM) types: Sesbania (G2) and cowpea (G3), with a control fallow (G1), and six nitrogen fertilization (NF) modules i.e. i.e. 0 kg N + 5 kg Zn ha -1 through bulk ZnO (N1), N through prilled urea (PU) (N2), N through PU + 5 kg Zn ha -1 through bulk ZnO (N3), 1% bulk ZnO-coated urea (N4), 0.1% nano ZnO-coated urea (N5) and 0.2% nano ZnO-coated urea (N6).The goal was to determine the best GM crops and NF modules for plant height, dry biomass, grain yield, milling quality, nutrient content, and nitrogen use efficiency (NUE). Results showed that combining G2 and N6 significantly improved plant height (13.34%) and dry biomass (38.1%) compared to G1 and N1. Overall, GM boosted grain yield by 12.75% over G1. Specifically, G2 had a yield 17.5% higher than G1. When it came to NF modules, zinc-coated urea led to a 10.03% yield increase over N2 and a 33.75% increase compared to N1. Using the N6 module enhanced hulling, milling, and head rice recovery by 3.73%, 4.45%, and 4.98%, respectively, over N1. Moreover, combining zinc with urea increased N content in milled rice by approximately 9.1% and enhanced the N, P, and K concentration in straw by 22.8%, 4.44%, and 11.8%, and the overall N, P and K uptake by 5.72%, 3.33%, and 11.7% compared to a combination of N1 and N2. Regarding NUE, GM showed better results in partial factor productivity (PFP) and recovery efficiency (RE) against G1, while other metrics remained similar. G2 as GM performed best in PFP and RE. The N5 module was optimal for NUE, though comparable to N6. In summary, using G2 as a GM and the N6 module optimally enhanced growth, yield, nutrient assimilation, and NUE in Basmati rice.